Degradation of soil microbiome and carbon dynamics in response to overgrazing in Austral wetland ecosystems - Toledo, Santiago; Diaz, Boris Gaston; Duarte Guardia, Sandra; Peri, Pablo Luis (Elsevier, 2025)
Wetlands (mallines) of Southern Patagonia are key ecosystems for biodiversity, forage production, and carbon (C) sequestration. However, overgrazing threatens their ecological integrity, causing varying levels of degra dation that alter soil physical, chemical, and biological properties. The impacts of grazing-induced degradation on soil microbiome function and C dynamics remain poorly understood. This study evaluated soil microbial attributes and C dynamics across eighteen wetlands under light, moderate, and severe degradation along a regional climatic gradient. Measured soil physicochemical and biological properties, such as microbial biomass C and N (MBC, MBN), basal respiration (SBR), microbial efficiency indices (qCO₂, qMC), and estimated both microbial and soil C stocks and CO₂ fluxes. Severe degradation reduced MBC and MBN by up to 46 % and 36 %, respectively, and SBR by 75 %, while increasing bulk density (0.57 to 0.92 g.cm− 3) and reducing nutrient levels (N: 80 %, P: 30 % and K: 35 %). Soil organic carbon (SOC) stocks and associated potential CO₂ removal were 2.5 to 3 times higher in lightly (8.63 and 31.68 kg.m− 2) degraded wetlands compared to moderate (4.52 and 16.59 kg.m− 2) and severe (2.75 and 10.08 kg.m− 2), respectively. Microbial efficiency declined with severe degradation, represented by low qCO₂ (0.13 µg.mg− 1) and high qMC values (1.35 %). Random Forest models identified bulk density, vegetation cover, soil N, and litter as key drivers of microbial and C-related processes. Our findings reveal that degradation alters the functional capacity of soil microbial communities, consequently affecting carbon sequestration. Microbial variables are early bioindicators of soil functional integrity. Integrating micro bial and soil physicochemical parameters into monitoring frameworks can help detect early degradation and guide sustainable land-use strategies for wetland ecosystems.